Determining River Floodway and its Role in Development Sustainability of Human Habitation (Case Study: Totshami) - Mojtaba Yamani; Amir Moradi; Saeed Rahimi herabadi (جغرافیا و پایداری محیط)
Flood hazards is considered as one of the environmental reactions in rivers system that has exceptional flow and severe. This type of hazard is a function of a particular period or place.Essentially, the most important reason for its formation is the geographical distribution of river floodplains and coastal lines along which provide an appropriate conditions for the development of post settlement. Hence, human interventions in the river channel and violation of its privacy has always caused the river limit to be in the center of attention. In the present study, Totshami river bank, located in Kermanshah province, has been chosen to assess the limit of flood processing for different return periods. In this regard, necessary statistics and information about the hydrology of the region were collected. Then they were analyzed, reconstructed and completed.In field surveys, a period of seven kilometers of river channels was chosen and their transverse profiles were drawn.Roughness coefficient confines of left and right channel was determined.Finally, using the HEC-RAS software, midst River floodgate for return periods 2, 5, 25, 50, 100 and 200 years was determined. In this paper, not only is the boundary map of the river bank for different return periods determined,but also it is tried to assess the relationship between the development process and the pathology of settlement nearby river flood. The results showed that the extent of river frontage Totshami processes in different return periods is considerably affected by geomorphologic characteristics the channel and floodplain area.Moreover, Privacy settlements in the river bank are 25 to 200 years.